(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objectives: We aim to investigate how antischemin preparation affects the platelet parameters in a rabbit model with alloxan induced diabetes. Methods: Rabbits were divided into 4 groups; group 1 or control group, group 2 or no antischemin group without medication, group 3 or experimental group and group 4 or comparing group. Specific parameters such as PLT, PWD, MPV, P-LCR and PCT concentration were measured on day 3, 7, 14, 21 and 28. Results: Treatment of the no antischemin group with 6% alloxan monohydrate only resulted in a significant increase of platelet level and reached the highest value at 28th days (336.5 ± 21.2). When animals pre-treated simultaneously with antischemin for 5 days, the level of platelets did not increase significantly, compared to that in the non-treated group. After treatment of this group with 6% alloxan monohydrate, at the end of the trial (28 day), the platelet level was 274.7 ± 6.2 g/L, and in the clopidogrel pre-treated group, it was 274 ± 13.9 g/L. In the non-treated group, during the first 21 days, alloxan monohydrate caused a slight increase in PDW levels. Conclusions: Numerous studies revealed that botanical extracts which have been widely used as medicinal agents show potent anti-diabetic activity. Due to the serious side effects or resistance on synthetic drugs that are used in diabetes, the approach of using herbal remedies could be a successful alternative to the currently available diabetic treatments.